Cognitive Flexibility, Relativistic Appreciation, and Ethnocultural Empathy Among Chinese International Students. (May 2020) - Liu, Shuyi; Wei, Meifen
Based on Berry's (1997) framework, we investigated the mediating effect of cognitive flexibility and the moderating effect of relativistic appreciation on the association between acculturative stress and ethnocultural empathy. A total of 199 Chinese international students from two Midwestern universities in the United States participated. Results indicated support for both hypotheses. First, cognitive flexibility significantly mediated the association between acculturative stress and ethnocultural empathy. Second, relativistic appreciation significantly moderated the effects of acculturative stress on ethnocultural empathy. Specifically, the effect of acculturative stress on ethnocultural empathy was significantly negative for those with relativistic appreciation levels below the 26th percentile. Conversely, this effect was not significant for those with relativistic appreciation levels above the 26th percentile. Our results offer a new perspective on acculturative stress, provides tools for clinicians working with Chinese international students who are coping with acculturative stress, and advocates for culturally appropriate coping strategies.